Accessing Reactive Metal Hydrides through Designed Heterometallic Bridges - Gonzalez, Fernando; De Leon, Edgardo; Shoshani, Manar M. (Synlett, 2024)
A methodology to access reactive hydride moieties is highly desirable, yet limited. Multimetallic hydride fragments are notable for their heightened reactivity and catalysis, but deliberate access to these species is lacking. In this highlight, we discuss recent developments by our group in the design of a new heterometallic complex that invokes an architecture designed to provide modular access to reactive hydride moieties by leveraging metal hydrides in combination with pendent donors to a model heterotrimetallic Ni–(Al–H)2 complex. An amplification of insertion-based reactivity has been examined in the hydrofunctionalization of quinolines, and our complex substantially outperformed the parent aluminum hydride LAlH (L = ligand). A potential rationale for the dramatically increased reactivity, and a further examination of these motifs and methodology in catalysis are also discussed.1. Introduction2. Heterometallic Hydride Design and Characterization3. Amplification in Catalysis4. Summary and Outlook
Keywords: heterometallics; cooperativity; hydrofunctionalization; hydrides; Lewis acids; base metals